Change in knee flexor torque after fatiguing exercise identifies previous hamstring injury in football players - Lord, C.; Ma'ayah, F.; Blazevich, A. J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Purpose: Muscular fatigue and inter-limb strength asymmetry are factors known to influence hamstring injury risk, however limb-specific exacerbation of knee flexor (hamstrings) torque production after fatiguing exercise has previously been ignored. To investigate changes in muscular force production before and after sport-specific (repeated-sprint) and non-specific (knee extension-flexion) fatiguing exercise, and explore the sensitivity and specificity of isokinetic endurance (i.e. muscle-specific) and single-leg vertical jump (i.e. whole limb) tests to identify previous hamstring injury. Methods: 20 Western Australia State League footballers with previous unilateral hamstring injury and 20 players without participated. Peak concentric knee extensor and flexor (180°·s-1) torques were assessed throughout an isokinetic endurance test, which was then repeated alongside a single-leg vertical jump test (SLVJ) before and after maximal repeated-sprint exercise. Results: Greater reductions in isokinetic knee flexor torque (-16%) and the concentric hamstring:quadriceps peak torque ratio (-15%) were observed after repeated-sprint running only in the injured (kicking) leg and only in the previously injured subjects. Changes in (1) peak knee flexor torque after repeated-sprint exercise, and (2) the decline in knee flexor torque during the isokinetic endurance test measured after repeated-sprint exercise, correctly identified the injured legs (N=20) within the cohort (N=80) with 100% specificity and sensitivity. Conclusion: Decreases in peak knee flexor torque and knee flexor torque during an isokinetic endurance test after repeated-sprint exercise identified previous hamstring injury with 100% accuracy. Changes in knee flexor torque, but not SLVJ, should be tested to determine its prospective ability to predict hamstring injury in competitive football players.